The role of chromium and nickel on the thermal and mechanical properties of FeNiCr austenitic stainless steels under high pressure and temperature: a molecular dynamics study. Issue 8 (24th May 2019) - Hasanzadeh, A.; Hamedani, A.; Alahyarizadeh, G.; Minuchehr, A.; Aghaei, M.
ABSTRACT: The effect of Cr and Ni content on thermo-mechanical properties of FeNiCr austenitic stainless steel under ambient and high pressure and temperature were investigated by MD simulations. The FCC structure was selected as optimum structure for FeNiCr system based on obtained MD results from Bonny EAM potential and valid experimental results. The structural and mechanical properties of pure Fe, Ni, and Cr were also estimated based on this potential, indicating good agreement with experimental results. These properties were computed for four experimental case studies which showed less than 10% error. Moreover, the elastic constants of the Fe–(8–18)Ni–(18–25)Cr systems were estimated. Results showed that bulk modulus increases by increasing the Ni and Cr contents, which can be connected to the changes in bonding electrons. The thermal properties of FeNiCr were calculated in ambient and high pressure. Although thermo-mechanical properties confirm good agreement with experimental results at the ambient condition, however, they indicate that FeNiCr Bonny potential is not applicable at high pressure. In order to tackle this issue, a hybrid potential was used at high Pressure/Temperature. The results illustrate enhanced mechanical properties, increase of melting point and reduction of LTE in high pressure and deteriorated mechanical properties at high temperature.